Ancient Jewish Historians and the German Reich : Seven Studies - Schwartz, Daniel R. (2024)
These seven studies analyze interpretations of ancient Jewish history by prominent Jewish scholars in the German world in the 19th and 20th centuries. Although focusing on diverse figures and episodes, they all argue that these scholars' views on the Jews' responses to Hellenistic and Roman rule, while built upon the ancient sources, were nurtured by contemporary notions concerning the options available to Jews living in a non-Jewish world.